The Ottoman Empire and the Bosnian uprising - Turhan, Fatma Sel (Library of Ottoman studies ;, 2014)
For the first time, Fatma Sel Turhan illuminates a period of crucial importance to the Balkan regions. She argues convincingly that the uprising was a response to Ottoman moves towards modernization designed to save the Ottoman Empire from decline, but which eventually led to its demise. She assesses how far the uprising can be considered a nationalist movement, who the rebels were, and how the central authorities dealt with and punished the perpetrators. The Ottoman Empire and the Bosnian Uprising is a major fresh contribution to our understanding of the late Ottoman world and the history of the Balkans.